Calorimetry in a Neutrino Observatory: The JUNO Experiment - Beatrice Jelmini (Instruments, 2022)
The Jiangmen Underground Neutrino Observatory (JUNO) is a multipurpose experiment under construction in southern China; detector completion is expected in 2023. JUNO is a homogeneous calorimeter consisting of a target mass of 20 kt of an organic liquid scintillator, aiming to detect antineutrinos from reactors to investigate the neutrino oscillation mechanism. The scintillation and Cerenkov light emitted after the interaction of antineutrinos with the liquid scintillator is seen by a compound system of 20 inch large PMTs and 3 inch small PMTs, with a total photo-coverage of 78%. A dual-calorimetry technique is developed based on the presence of the two independent photosensor systems which are characterized by different average light level regimes, resulting in different dynamic ranges. Thanks to this novel technique, an unprecedented high light yield, and in combination with a comprehensive multiple-source and multi-position calibration campaign, JUNO is expected to reach energy-related systematic uncertainties below 1% and an effective energy resolution of 3% at 1%, required for the neutrino oscillation analysis.